2019
DOI: 10.1038/s41385-019-0139-3
|View full text |Cite
|
Sign up to set email alerts
|

PAD4-dependent NETs generation are indispensable for intestinal clearance of Citrobacter rodentium

Abstract: Peptidyl arginine deiminase-4 (PAD4) is indispensable for generation of neutrophil extracellular traps (NETs), which can provide antimicrobial effects during host innate immune response; however, the role of PAD4 against gastrointestinal infection is largely unknown. Herein, we challenged PAD4-deficient ( Pad4 −/− ) mice and wild-type (WT) littermates with Citrobacter rodentium ( CR ), and investigated bacteria clearance and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
24
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 47 publications
(27 citation statements)
references
References 54 publications
3
24
0
Order By: Relevance
“…This includes cancer, chronic, autoimmune and neurodegenerative diseases [ 19 , 20 , 23 ], CNS injury [ 24 , 25 , 26 ] and ageing [ 27 , 28 ]. Importantly, roles for PADs have been described in viral [ 29 , 30 , 31 ] and other pathogenic infections, including sepsis, endotoxemia [ 29 , 32 , 33 , 34 , 35 , 36 , 37 , 38 ] and antibiotic resistance [ 39 ]. The roles for PADs in anti-viral responses include PAD-mediated neutrophil extracellular trap formation (NETosis), for example, in respiratory syncytial virus disease [ 40 ].…”
Section: Introductionmentioning
confidence: 99%
“…This includes cancer, chronic, autoimmune and neurodegenerative diseases [ 19 , 20 , 23 ], CNS injury [ 24 , 25 , 26 ] and ageing [ 27 , 28 ]. Importantly, roles for PADs have been described in viral [ 29 , 30 , 31 ] and other pathogenic infections, including sepsis, endotoxemia [ 29 , 32 , 33 , 34 , 35 , 36 , 37 , 38 ] and antibiotic resistance [ 39 ]. The roles for PADs in anti-viral responses include PAD-mediated neutrophil extracellular trap formation (NETosis), for example, in respiratory syncytial virus disease [ 40 ].…”
Section: Introductionmentioning
confidence: 99%
“…14 Recently, it has been shown that C. rodentium triggers NETosis in vitro and that NET formation is required for clearance in vivo. 15,16 Both NETosis and degranulation results in the release of reactive oxygen and nitrogen species (ROS and RNS), peroxidases including myeloperoxidase (MPO) and proteolytic enzymes such as neutrophil elastase (NE), cathepsin G and proteinase 3, which are contained within azurophilic granules. 17,18 These potent agents are unable to distinguish host cells from bacterial targets and if not tightly controlled have damaging consequences on host tissue.…”
Section: Introductionmentioning
confidence: 99%
“…Non‐DNA‐bound histones can subsequently break the nuclear envelope and plasma membranes 56 . The inability for PAD4‐deficient mice to form NETs in response to ionomycin shows the critical role PAD4 plays in this process 50,57 . In line with this, inhibition of PAD4 by the known PAD4 inhibitor Cl‐amidine significantly reduces histone citrullination and prevents the formation of NET‐like structures after stimulation of neutrophils with ionomycin 58 …”
Section: Pad4 In Net Formationmentioning
confidence: 95%